As the yellow rattle ripens’: Gardening craft as socio-ecological place-making - Cele, Sofia (FormAkademisk, 2023)
This paper focuses on the doing of gardens and explores how amateur gardeners relate to gardening craft in their everyday garden practices. Based on qualitative empirical work, this paper discusses how different craft methods and caring practices are employed as memory work and as a means to connect to, and create, the garden as a socio-ecological place. Based on the gardeners’ narratives, the garden is discussed as a web of self and a place where the meeting between the gardener and the more-than-human are central incentives to gardening. Gardening is an active place-making that goes beyond modifying the materiality of place. Rather, garden craft is narrated as reflecting the gardeners’ underlying relationship to and understanding of plants, soil and animals. It is the means through which gardeners connect in an embodied way to ‘the nature’ of the garden. Garden craft is proposed as an art that is passed on between generations. Gardening craft can be improved by an increased understanding of the temporality of the garden and by developing a sensitivity towards the complex socio-ecological relationships that shape a place. It is concluded that garden craft is understood as central not only to how the garden is constructed as a place but also to how the gardener relates to the garden as affecting, and being affected by, the current environmental crisis.